PEMANFAATAN WHATSAPP GROUP SEBAGAI SARANA KOMUNIKASI GURU DAN ORANGTUA SISWA SELAMA MASA PANDEMI COVID 19 - Dwhy Dinda Sari (Unit Pelaksana Praktik Kependidikan Terpadu Fakultas Keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Riau, 2021)
The development of increasingly sophisticated technology has a positive impact on life, including in communication activities. The Whatsapp application is one of the most used applications today. All ages and professions are familiar with the use of Whatsapp. This study aims to determine the characteristics of the use of WhatsApp and to determine the use of WhatsApp Group social media in PAUD parents and teachers as a medium of communication. The method used in this research is descriptive qualitative by describing, recording, analyzing and interpreting the conditions that are happening. The results showed that the use of the WhatApp Group social media in PAUD was very large. Apart from serving as a function of conveying information, WhatsApp Group also functions as a medium for discussion and a medium for sharing, as a medium of entertainment and as a medium that parents can use to monitor their children while at school.